2009
DOI: 10.1080/00015458.2009.11680522
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Digestive Continuity after Hartmann’s Procedure: ASA Score is a Predictive Factor for Risk of Postoperative Complications

Abstract: The RDC is an intervention performed safely after a 3 to 5-month delay with acceptable morbidity and negligible mortality. The ASA score is a determining factor for the risk of complications (p < 0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The length of intensive care unit (ICU) stay was also significantly ( p = 0.003) shorter in the LG [LG 0 days (0–2); OG 1 day (0–12)]. Significant advantages associated with a laparoscopic procedure were observed for the return to normal bowel function (measured as a clinical parameter by bowel sounds; LG 3 days [2–4]; OG 4 days [2–9]; p < 0.0001), the return to normal diet (LG: 3 days [2–6]; OG 4 days [2–10]; p = 0.001), and in the postoperative continuous use of analgesics (non‐steroidal anti‐inflammatory drug [NSAID] or morphine preparations) in days (LG 7 days [6–10]; OG 12 days [6–30]; p < 0.0001). The length of the overall hospital stay (LOS) was also significantly shorter in the LG, with a median of 9 days (7–14) compared with 15 days (8–163) in the OG ( p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The length of intensive care unit (ICU) stay was also significantly ( p = 0.003) shorter in the LG [LG 0 days (0–2); OG 1 day (0–12)]. Significant advantages associated with a laparoscopic procedure were observed for the return to normal bowel function (measured as a clinical parameter by bowel sounds; LG 3 days [2–4]; OG 4 days [2–9]; p < 0.0001), the return to normal diet (LG: 3 days [2–6]; OG 4 days [2–10]; p = 0.001), and in the postoperative continuous use of analgesics (non‐steroidal anti‐inflammatory drug [NSAID] or morphine preparations) in days (LG 7 days [6–10]; OG 12 days [6–30]; p < 0.0001). The length of the overall hospital stay (LOS) was also significantly shorter in the LG, with a median of 9 days (7–14) compared with 15 days (8–163) in the OG ( p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…The length of the interval before Hartmann reversal is determined by the underlying disease itself and the physical status of the patient [12]. A review of the literature revealed that most surgeons recognize an interval of 15-17 weeks after the initial Hartmann procedure as ideal for the most common indication, perforated sigmoid diverticulitis.…”
Section: Discussionmentioning
confidence: 99%
“…Restoring intestinal continuity after Hartmann's operation is a difficult operation that is associated with a high morbidity rate, with anastomotic leakage rates ranging from 4% to 16% and an operative mortality reported as high as 10% [7][8][9][10].…”
Section: Reversal Of Hartmann's Proceduresmentioning
confidence: 99%
“…ASA score consists of five classes (I to V) as follows: in class I, the patient is completely fit for surgical operation, class II patient has only mild systemic disease, class III patient has severe systemic disease that is not disabling, class IV patient has severe systemic disease that confers impending threat to life, class V a severe morbid condition that the patient is not anticipated to live 24 hours with or without surgery [ 7 ]. Reversal of Hartmann’s procedure and restoration of colonic continuity was associated with relatively high morbidity and mortality rates [ 8 , 9 ]. Reversal of Hartmann’s procedure could be done by either open surgery approach or laparoscopic approach [ 10 ].…”
Section: Introductionmentioning
confidence: 99%